Peculiarities of the State of Dental Patients with Hepatitis B. Botkin's Disease - Abdusalomova M.U. (Scholars Digest Publishing, 2023)
To date, as a result of numerous clinical and experimental studies, a relationship has been established between changes in the oral cavity and the pathology of internal organs. In modern dentistry, interest in research on comorbidities is explained by the accumulation of new arguments, the emergence of new information in the system of the whole organism. In this regard, questions about the relationship between diseases of internal organs, in particular the liver and oral cavity organs, are relevant. The development of mucosal lesions and inflammatory diseases of the periapical tissues of the oral cavity (in particular, complications that occur after tooth extraction) aggravates the course of the underlying disease and are features of therapeutic and preventive measures [1].
Keywords: Dentistry, prevention, treatment, health, hepatitis B, Botkin's disease.